Динамічні процеси в говорах Прикарпаття - Лесюк, М.П. (Мовознавство, 2011)
У статті схарактеризовано основні спільні й відмінні риси говорів Прикарпаття, обґрунтовується думка про історичну основу цих рис, запропоновано дещо відмінний від традиційного погляд на діалектні континуанти деяких праслов’янських голосних, ідеться про зміни, нівеляцію діалектних форм під впливом літературної мови. The main common and different features of the vernaculars of Precarpathia have been characte-rized in the article. The idea of the historical basis of these features has been proved. The article suggests a new, somewhat different from traditional, approach to the dialectal continuants of some Old Slavonic vowels. Finally, it deals with the changes in dialectal forms and their levelling under the influence of literary language.